ANALISIS INDEKS KEPUASAN MASYARAKAT DALAM PELAYANAN PEMBUATAN E-KTP DI KABUPATEN SUMEDANG - Fathoni, Abdurrahmat; Solahudin, Imam; Fatimah, Linda Rosmawati (JRPA - Journal of Regional Public Administration, 2021)
This study aims to determine the service of the Population and Civil Registration Service of Sumedang Regency which is measured based on community satisfaction using the Community Satisfaction Index.This research is a descriptive type of research using the Community Satisfaction Index analysis with the results of the data in the form of numbers. This research was conducted at the Department of Population and Civil Registration of Sumedang Regency in November 2020. The sampling technique used was non-probability sampling with accidental sampling type. The data collection technique is done by using a questionnaire or questionnaire technique. The results showed that the value of the Community Satisfaction Index (IKM) for the Sumedang Regency Population and Civil Registration Service was 2.918 with a conversion rate of 72.95. Then the performance of public services is in the category of good service quality. The results of the 14 indicators of the Community Satisfaction Index with a value range between 0-100 are as follows: (1) the service procedure has an IKM value of 68.75 in the good category; (2) the service requirement has an IKM value of 73.00 in a good category; (3) clarity of service officers has an IKM score of 73.25 in a good category; (4) discipline of officers has an IKM score of 76.50 in a good category; (5) the responsibility of officers has an IKM score of 75.00 in a good category; (6) the ability of officers to have an IKM score of 76.00 in a good category; (7) the speed of service has an IKM value of 66.00 in the good category; (8) justice in getting services has an IKM value of 70.50 in a good category; (9) politeness and friendliness have the IKM score of 75.75 in the good category; (10) fairness of service fees has an IKM value of 74.25 in a good category; (11) certainty of service costs has an IKM value of 73.50 in a good category; (12) schedule certainty has an IKM value of 70.50 in a good category; (13) environmental comfort has an IKM value of 78.50 with a good category; (14) service safety has an IKM value of 78.00 in a good category